Be a soldier of truth - Omer, Spahic (IIUM Today, 2019)
Life is an endless and multi-tiered confrontation between good and evil. It is a battleground in every sense of the word. Almighty Allah says that He created life and death “to put you to the test and see which of you is most virtuous in your deeds” (al-Mulk, 2). As such, this life is the only opportunity to secure the pleasure and blessings of the Creator and the bliss of the Hereafter. Man is the main protagonist in such a state of affairs. He is the most restive, fretful and anxious being. That is why sometimes, with proper guidance and virtue on-board, man can be like an angel, but at other times, without proper guidance and virtue, he can be worse than devil. He can be the worst and most dangerous animal. As Aristotle once said, without virtue, man is the most unholy and the most savage of animals, and the worst with regard to lust and gluttony. Mark Twain also said that “of all the animals, man is the only one that is cruel. He is the only one that inflicts pain for the pleasure of doing it.” Hence a Latin proverb “Homo homini lupus”, which means “A man is a wolf to another man.” Both Sigmund Freud and Thomas Hobbes – among others – subscribed to the message of the maxim. At any rate, life is what life is and what its Creator wanted it to be. It is not what we ineptly perceive, or as a result of our fantasies would like it to be. Life is an objective reality. It is not simply a subjective state existing in the “mind of the perceiver”.